2016
DOI: 10.1051/matecconf/20163803001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hybrid Fibre Reinforcement on Fire Resistance Performance and Char Morphology of Intumescent Coating

Abstract: Abstract. Recent researches of fire retardant intumescent coatings reinforced by single Rockwool and single glass wool fibre at various weight percentages and lengths showed some improvements to the mechanical properties of the coatings and the char produced. Therefore, in this research the fibres were combined together in intumescent coating formulation at several weight percentages and fibre lengths to study their effects towards fire resistance performance and char morphology. The hybrid fibre reinforced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Because char foam acts as a physical barrier to heat and mass transfer, it interferes with the combustion process [73,97,123]. As mentioned earlier, three elements are required for a mixture to be an efficient intumescent system: inorganic acid (dehydrating agent), blowing agent (spumific), and carbon-rich polyhydric material as a char former (carbonific) [124,125]. The ratios in which the various compounds are present are also a critical concern, where the best ratio has to be resolved experimentally.…”
Section: Physical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because char foam acts as a physical barrier to heat and mass transfer, it interferes with the combustion process [73,97,123]. As mentioned earlier, three elements are required for a mixture to be an efficient intumescent system: inorganic acid (dehydrating agent), blowing agent (spumific), and carbon-rich polyhydric material as a char former (carbonific) [124,125]. The ratios in which the various compounds are present are also a critical concern, where the best ratio has to be resolved experimentally.…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…The ratios in which the various compounds are present are also a critical concern, where the best ratio has to be resolved experimentally. One or more of these substances could be substituted for others in the same class or group in which further research has revealed that incorporating As mentioned earlier, three elements are required for a mixture to be an efficient intumescent system: inorganic acid (dehydrating agent), blowing agent (spumific), and carbon-rich polyhydric material as a char former (carbonific) [124,125]. The ratios in which the various compounds are present are also a critical concern, where the best ratio has to be resolved experimentally.…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…It suggests that the reactivity of this fiber is quite limited and only the very surface of the fiber can react with derivatives of APP at high temperatures. In fact, the rod-shaped fiber was more likely to play a role of physically reinforcing the network to keep the char integrity [44,47]. Thus, without the support of the fiber (i.e.…”
Section: Physical Appearance Of the Intumescent Charsmentioning
confidence: 99%
“…According to the previous reports, bagasse has many peculiarities, such as renewability, tenacious, biocompatibility and environmental friendliness. Thus, the bagasse was used to enhance the mechanical strength, aging resistance and so on 20 …”
Section: Introductionmentioning
confidence: 99%